Preparation and characterization of LaFeO3 dual complexing agents for photodegradation of humic acid - Mika Angelika O Enriquez, 1995- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Kimia - Gas)) - Universiti Teknologi Malaysia, 2018